Warden [videorecording (DVD)] - Juhasz, Jeff; De Lorenzi, Giovanni; Willow, Alli; Saboia, Antonio, 1985- (Freestyle Digital Media, 2025)
"Warden" is a faux documentary exploring the real-world impact of a young man discovering his superpowers. It delves into how his presence influences society, attracting followers, sparking conflict, and changing the lives of everyone around him.